A Systematic Literature Review on Methodologies for Improving Software Quality in Software Development Process - Inam Ul Haq; Waseem Abbas; Mehran Mehran Shakoor; Wasi Butt (NUML International Journal of Engineering and Computing)
For better repute in software monopoly, quality of product is one of the essential factors in any corporation. Quality of the product depends on the satisfaction of customer. Product quality is measured by customer satisfaction with that product. The goal of quality might be attained only over convenient fundamentals and policies. The enormous and developing nations are making improvements on every day for improving the quality of the products they manufactured to increase the satisfaction of their customers. Every corporation tries their best to design quality software that best suits to customer needs. For the purpose of better quality, some fundamentals and policies were made, however there might be distinct problems, there are several rationales for poor quality of product. We choose quantitative approach of research as methodology for our research. Basically, quantitative approach focuses on measuring and evaluating the data. This paper will address different issues that were corresponding to these rationales. Several techniques will also be explained, as well some alternative solutions are defined in this paper that will leads to good quality of any product or software. Furthermore, we conclude that systematic approach and incremental approach, these are good but the problem with these approaches is that requirements will be freeze. It will be complex and problematic to accommodate changes. In short, all techniques have their own impact on enhancement of software quality.